EDU-GARDEN TRAINING FOR SUPPORTING ISLAMIC BASIC EDUCATION IN MEDAN - Suwantoro, Hajar; Achmad, Nurman (Talenta Publisher, 2018)
Community service activities are focused on the problem of enriching the understanding and practice of making governance a simple garden, edu-garden, which can be done by the students of primary school in Medan city rural areas, with the conditions of the lack of urban green areas as well as the mandate of the national education, 2013 to make education sustainable environment-based vocational called as Adiwiyata school. Partnering with school teachers MIS Al Hidayah Medan Johor and Medan Selayang, be forming edu-garden as an alternative to the procurement of the garden utilizing household waste. Minimal conditions to the availability of land recycling infrastructure can be used for urban green movement through practical training programs edu-garden forming by utilizing waste for gardening activities. The result is the creation of edu-garden forming by teachers and students as teaching materials module based educational environment. The results of the simulation training and edu-garden forming this a viable alternative layout creation of urban green neighborhoods in order to achieve environmental health and public welfare.